Can social accountability mechanisms using community scorecards improve quality of pediatric care in rural Cambodia?. (27th June 2020) - Edward, Anbrasi; Jung, Younghee; Chhorvann, Chea; Ghee, Annette E; Chege, Jane
Abstract: Objective: To determine the effect of social accountability strategies on pediatric quality of care. Design and Setting: A non-randomized quasi experimental study was conducted in four districts in Cambodia and all operational public health facilities were included. Participants: Five patients under 5 years and their caretakers were randomly selected in each facility. Interventions: To determine the effect of maternal and child health interventions integrating citizen voice and action using community scorecards on quality of pediatric care. Outcome Measures: Patient observations were conducted to determine quality of screening and counseling, followed by exit interviews with caretakers. Results: Results indicated significant differences between intervention and comparison facilities; screening by Integrated Management of Childhood Illness (IMCI) trained providers (100% vs 67%, P  < 0.019), screening for danger signs; ability to drink/breastfeed (100% vs 86.7%, P  < 0.041), lethargy (86.7% vs 40%, P  < 0.004) and convulsions (83.3 vs 46.7%, P  < 0.023). Screening was significantly higher for patients in the intervention facilities for edema (56.7% vs 6.7%, P < 0.000), immunization card (90% vs 40%, P  < 0.002), child weight (100 vs 86.7, P  < 0.041) and checking growth chart (96.7% vs 66.7%, P  < 0.035). The IMCI index, constructed from key performance indicators, was significantly higher for patients in the intervention facilities than comparison facilities (screening index 8.8 vs 7.0, P  < 0.018, counseling index 2.7 vs 1.5, P  < 0.001). Predictors of screening quality were child age, screening by IMCI trained provider, wealthier quintiles and intervention facilities. Conclusion: The institution of social accountability mechanisms to engage communities and facility providers showed some improvements in quality of care for common pediatric conditions, but socioeconomic disparities were evident.